Companion of the 2018 ACM/IEEE International Conference on Human-Robot Interaction 2018
DOI: 10.1145/3173386.3177057
|View full text |Cite
|
Sign up to set email alerts
|

Explanations and Expectations

Abstract: Trust is a vital determinant of acceptance of automated vehicles (AVs) and expectations and explanations are often at the heart of any trusting relationship. Once expectations have been violated, explanations are needed to mitigate the damage. This study introduces the importance of timing of explanations in promoting trust in AVs. We present the preliminary results of a within-subjects experimental study involving eight participants exposed to four AV driving conditions (i.e. 32 data points). Preliminary resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…For instance, empirical results from a series of studies on explanations by automated vehicles show how the explanations' timing plays a central role in determining users' trust. The researchers found that explanations provided before the vehicle acted had a positive influence on participants' attribution of trust, while explanations that were given after a specific action did not affect trust ratings [41,42]. In line with H1 , these findings suggest that explanations may be more beneficial before, rather than during, an interaction.…”
Section: Trust Development Over Timementioning
confidence: 70%
See 1 more Smart Citation
“…For instance, empirical results from a series of studies on explanations by automated vehicles show how the explanations' timing plays a central role in determining users' trust. The researchers found that explanations provided before the vehicle acted had a positive influence on participants' attribution of trust, while explanations that were given after a specific action did not affect trust ratings [41,42]. In line with H1 , these findings suggest that explanations may be more beneficial before, rather than during, an interaction.…”
Section: Trust Development Over Timementioning
confidence: 70%
“…In this regard, several researchers note that, particularly during the first phases of the adoption of and interaction with new AI-based technologies, providing initial explanations may improve trust formation processes. For instance, studies suggest that automated vehicles' explanations provided before the vehicle acted may positively influence the willingness to trust the vehicle [41,42]. Specifically, by compensating for the lack of previous experience (and proven reliability), initial explanations that clarify the functions and purposes of a specific technology may reduce users' perception of risk, increase perceived trustworthiness, enable accountability, and mitigate individual disposition [25,34,43].…”
Section: Initial Trustmentioning
confidence: 99%
“…In XAI, transportation is an important application area. The explanation of car behavior has even now begun, [137,138], but there is still a long way to go.…”
Section: Xai For Transportationmentioning
confidence: 99%
“…According to the literature, there are four reasons for the need for XAI, depending on the motivation (Bojarski et al. , 2016; Haspiel et al. , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to the literature, there are four reasons for the need for XAI, depending on the motivation (Bojarski et al, 2016;Haspiel et al, 2018). The first is to explain or justify, which implies a solution to the problem of unobjective or discriminatory results that presupposes a particular outcome's validity, proving that the algorithms are fair and ethical (Huston, 2021).…”
Section: Theoretical Background 21 Importance Of Explainable Artifici...mentioning
confidence: 99%